Endoscopic Findings Associated With Button Battery Ingestion in Children: Do We Need to Change the Protocol for Managing Gastric Location?. Issue 11 (November 2020) - Ríos, Gloria; Rodríguez, Lorena; Lucero, Yalda; Miquel, Isabel; Arancibia, María Eugenia; Alliende, Francisco
Abstract : Background: Ingested button batteries (BB) can cause corrosive damage of digestive mucosa within minutes. Immediate endoscopic removal of esophageal BB has been clearly established, but the management of BB located in the stomach is still controversial. Aim: To describe demographic, clinical, radiologic, and endoscopic characteristics of a series of pediatric patients evaluated for BB ingestion. Methods: Retrospective analysis of clinical charts belonging to children younger than 15 years, who underwent endoscopic removal of BB at Clínica Alemana of Santiago, between November 2007 and November 2011. Results: Twenty-five patients subjected to upper endoscopy were analyzed; median age, 31 months; 15 were male (60%), and 11 patients (46%) were symptomatic after ingestion. The BB ingestion was confirmed by radiograph. Endoscopy revealed 10 patients with BB in the esophagus, 12 patients in the stomach and 3 distal to duodenum. Range time between ingestion and endoscopy was 2 to 10 hours for esophageal BB and 2 hours to 3 days for gastric BB. Eight of the 22 BBs removed had a diameter of 20 mm or greater, 6 of them were located in the esophagus and 2 in stomach. The BB color changes were observed in 14 of the 22 BBs. Breakage of battery edges was present in 11 of the 22 batteries. All patients with esophageal BB and 6 of those 12 with gastric BB presented mucosal damage. Conclusion: Esophageal BB cause damage within hours. The BB located in the stomach may also cause damage early. Extraction of gastric BB before 48 hours should be considered.